Impact of the national vaccination campaign against COVID-19 on patient attendance to the emergency department of the Pediatric Emergency Hospital - Stramandinoli, Angela (2023)
Objective: To analyze the variation in attendance and diagnoses after the national vaccination campaign against COVID-19 in the pediatric emergency department. The study: Analytical retrospective cross-sectional study. Pediatric emergency department visits were compared between epidemiological weeks 1 and 52 of the years 2020 and 2021, analyzing sociodemographic characteristics, condition and diagnosis. Chi-square was used for bivariate analysis. Findings: A 77.8% increase was found in the number of attentions during the year 2021 compared to 2020. There was a 4% increase in infectious diseases and a 9.2% increase in respiratory diseases. In addition, a decrease of 8.7% was observed in gastrointestinal diseases. Conclusion: The results indicate that after the start of the national vaccination campaign, there was a significant increase in the number of patients compared to 2020, mainly for respiratory and infectious or parasitic diseases.